A review on methods for obtaining dynamical property parameters of machining processes. (1st July 2023) - Ren, Yuan-Yuan; Wan, Min; Zhang, Wei-Hong; Yang, Yun
Abstract: Accurately obtaining dynamical parameters in relation to machining processes is extremely crucial to predict stability lobe diagrams (SLDs), which are used to plan chatter-free cutting parameters. Existing progress reviews on machining chatter mainly focus on the methods for detecting, monitoring and predicting chatter, especially including algorithms for predicting SLDs. However, a comprehensive review of techniques oriented for obtaining dynamical parameters during machining processes is still desired. This article presents a systematic review on typical means for obtaining typical dynamical parameters, and provides adequate guidance for studying the chatter problem of machining processes. Experiment-based feature collecting and theoretically formulating methodologies for figuring out dynamical parameters are outlined and compared with each other. Comments and discussions are conducted by deeply reviewing relevant methods for obtaining FRFs of the tool–holder–spindle system, property parameters of the process damping and FRFs of the thin-walled workpiece. Kernel procedures and key algorithms for evaluating dynamical parameters are provided. Advantages and disadvantages of different methods are analyzed. Finally, challenges for obtaining dynamical parameters are discussed, and potential research directions are suggested. Appropriate techniques for obtaining dynamical parameters will certainly enhance the accuracy of the predicted SLDs for developing chatter suppressing means in various machining operations.